Epithelioid Hemangioma In A Male Hound Dog: A Case Report - Dhoke, V. S.; Pande, P. R.; Hedau, Madhuri; Ingole, R.S.; Joshi, M.V. (Indian Journal of Veterinary Sciences and Biotechnology, 2016)
Hemangiomas are benign neoplasms of vascular endothelium often found in the skin of dogs (Goldschmidt and Hendrick, 2002; Zachary and McGavin, 2012). Hemangioma arises from vascular endothelial cells of the dermis or subcutaneous tissues in about equal frequency. There is no sex predilection for the presence or absence of hemangiomas. The average age of affected dog is nine years, though the tumor may develop in much younger dogs (Meuten,2002). A wide variety of dog breeds are affected, but Italian Grey hounds and Whip pets are over represented (Schultheiss, 2004). Hemangiom as are ovoid or discoid in shape, moderately firm and they are reddish black and blood oozes from the surface. In dogs hemangiomas are typically benign, solitary, deep dermal tumors (Cooley et al., 1997). Diagnosis of skin tumors usually includes evaluation of cells using cytology and histopathology in cases where a biopsy is taken, Paucity of tumor in Hound dogs prompted us to put on record a case of epithelioid hemangioma in this breed.